DOI: 10.24124/2021/59180
|View full text |Cite
|
Sign up to set email alerts
|

"Being connected to my Shuswap family in the south": a reflective inquiry into the social media experiences of Indigenous youth in Northern and rural British Columbia

Abstract: This research extends and explores two key concepts. First, cultural preservation is important to Indigenous health and wellbeing. Second, when Indigenous youth spend quality time (whether online or offline) on issues pertaining to their identity and sense of self, that time can be key to preserving Indigenous cultures. This research project was an exploratory study carried out using a variety of research methods, including online surveys, semistructured interviews, and open ended storytelling engagements. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 91 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…Importantly, it is shown that societal recognition of an individual's minority language increases self-esteem (Baker, 2003;Csata, Hlatky, & Liu, 2022;McDermott & Craith, 2022), and this has been demonstrated within the social media context, also (Odulaja, 2021). Although Chapter Two goes into greater detail, it is possible a FLW perceiving fewer opportunities to use Welsh on social media might consider his or her first language not fully recognized by society, thereby reducing level of self-esteem (e.g., Baker, 2003).…”
Section: Contextual Overview Of the Thesismentioning
confidence: 90%
See 4 more Smart Citations
“…Importantly, it is shown that societal recognition of an individual's minority language increases self-esteem (Baker, 2003;Csata, Hlatky, & Liu, 2022;McDermott & Craith, 2022), and this has been demonstrated within the social media context, also (Odulaja, 2021). Although Chapter Two goes into greater detail, it is possible a FLW perceiving fewer opportunities to use Welsh on social media might consider his or her first language not fully recognized by society, thereby reducing level of self-esteem (e.g., Baker, 2003).…”
Section: Contextual Overview Of the Thesismentioning
confidence: 90%
“…In addition to the above possible reason why FLWs might use social media more, there exist numerous other reasons why a FLW might use social media more often. Odulaja (2021) observed how use of one's native language on social media promoted self-esteem, which is suggestive of an intrinsic human need. This would make sense when one considers Maslow's (1943) hierarchical needs model, which is a five-tiered model moving from an individual's lowest order needs (physiological needs relating to air, water, food, shelter, sleep, etc.)…”
Section: Social Media Dependencymentioning
confidence: 96%
See 3 more Smart Citations